PERAN PEMBERDAYAAN BANK SAMPAH DALAM ISLAM (STUDI KASUS PADA BANK SAMPAH INDUK SURABAYA) - Ahmad Thoriq Alfarisyi; R. Moh. Qudsi Fauzi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This research aims to describe the role of Bank sampah induk Surabaya in empowering the customer's economy from an Islamic perspective. Viewed from an increase in customer empowerment by maddi (material) and ma'nawi (non material). This research uses a descriptive qualitative approach with a case study method. The results of this study were that the four informants experienced increased fulfillment of basic needs, increased income, increased strength, and increased charity, as well as increased environmental hygiene security after joining as customers of Bank sampah induk Surabaya. Maddi (material), managing and sorting its own waste into an economically valuable item and can be saved, it is clear that the empowerment carried out by the Bank Sampah Induk Surabaya is able to improve the economy of its customers in groups and individuals. and ma'nawi (non material), the maintenance of environmental security is the most obvious impact felt by the reduction in the amount of waste because people are beginning to realize the importance of protecting the environment. In addition, by saving in a waste bank, customer charity will also increase along with the increase in people's income.Keywords: Role of Waste Bank, Empowerment in Islamic Perspective, Economy of Natural Resources and Environment, Customer WelfareREFERENCESAryeti. 2011. Peningkatan Peranserta MasyarakatMelalui Gerakan Menabung pada Bank Sampahdi Kelurahan Babakan Surabaya, Kiaracondong Bandung. Jurnal Permukiman, Vol. 6 No. 1 April2011.Departemen Agama RI, Al-Quran dan Terjemahannya (Jakarta: CV Darus Sunnah, 2002)Fatwa MUI Nomor 47 Tahun 2014 tentang Pengelolaan Sampah Untuk Mencegah Kerusakan Lingkungan Pasal 2 ayat 1 dan 4. Kementrian Lingkungan Hidup RI. (2011). BankSampah dan 3R : Membangun Lingkungandan Ekonomi Kerakyatan.Labib, Mz. 2006. Etika bisnis dalam islam. Surabaya: Bintang Usaha Jaya.Sabiq, Sayyid. 1988. Fikih Sunnah (jilid 12). Bandung: Al-Ma’arif.___________. 2006. Fiqih Sunnah. (Jilid 4). Jakarta: Pena Ilmu dan Amal.Sanrego, Yulizar D. dan Moch Taufik. 2016. Fiqih Tamkin (Fiqih Pemberdayaan), Jakarta: Qisthi Press.Sanrego, Yulizar. 2016. Fiqih Tamkin (Fiqih pemberdayaan) membangun modal social dalam mewujudkan khiru ummah. Jakarta: Qisthi Press.Sudrajat, H.R. 2009. Mengelola Sampah Kota, Jakarta: Penebar SwadayaSugiyono. 2005. Memahami Penelitian Kualitatif. Bandung: PT Remaja Rosidakarya. ________. 2009. Metode Penelitian Bisnis. Bandung : Alfabeta.Suwerda, Bambang. 2012. Bank Sampah (kajian teori dan penerapan).Yogyakarta: Pustaka Rihama.Syafe’i, Agus Ahmad dan Nanich Machendra. 2001. Pengembangan Masyarakat Islam. Bandung: Rosdakarya, cetakan ke 1,Syafe’i, Rachmat. 2000. Fiqh Muamalah. Bandung: CV Pustaka Setia.Yin, K. Robert. 1987. Case Study Research Design and Methods, terjemahan M. Djauzi Mudzakir. 2013. Jakarta : PT. Raja Grafindo Persada.____________. 2009. Case Study Research : Fourth Edition. United States : Sage Inc.____________. 2006. Case Study Research Design and Methode : Second Edition. United States : Sage Inc.Yusuf Qardhawi, Muhammad. 1993. Halal dan Haram dalam Islam. Jakarta; PT Bina Ilmu. hlm.383.